(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
In an induced myocardial ischaemic shock- in 43 rats, 21 died from ventricular fibrillation. The other (22) went into very severe systemic hypotension and A. V. block which later led to asystole. Marked ventricular ectopic activity, including isolated extrasystoles and a burst of ventricular tachycardia began to show around 5-7 minutes after coronary artery ligation associated with marked ST depression, in all the animals. The extrasystoles occurred between 5 and 18 minutes with a peak ectopic count of 211 per minute at around 11 minutes of ligation. By 30 minutes of ligation, the animals, which survived, returned to a stable sinus rhythm. This study presents a useful model for assessing myocardial ischaemic investigations leading to a possible timing of clinical intervention during a sudden cardiac arrest.